Generalized anxiety disorder among people living with HIV receiving highly active antiretoviral therapy / Nor Hidayah Jaris and Salmi Razali - Jaris, Nor Hidayah; Razali, Salmi (2021)
Generalized anxiety disorder is the most prevalent anxiety disorder that may worsen psychological well-being and physical conditions of people living with Human Immunodeficiency Virus (PLHIV). There is sparse knowledge on factors contributing to this mental illness for preventive measures and evidence-based interventions. The study aimed to determine the prevalence of generalized anxiety disorder or GAD and its contributing factors among PLHIV receiving Highly Active Antiretroviral Therapy (HAART). This was a crosssectional study of 210 PLHIV who sought treatment at the Infectious Disease Clinic in one of the public hospitals in Malaysia. Patients who fulfilled the inclusion criteria and consented were assessed for socio-demographic characteristics and clinical factors using Pro Forma questionnaires and face-to-face interviews, supplemented with data from medical records. Visual analogue scale, Hospital Anxiety Depression Scale and Multidimensional Scale of Perceived Social Support were used to determine adherence to treatment, level of anxiety and level of support system, respectively. Mini International Neuropsychiatric Interview was used to diagnose GAD. 28 (13%) participants had GAD. After controlling for confounders, multivariate analysis indicated that illicit substance used in the past (AOR=4.17; p=0.003; 95% CI=1.56-9.44) and a low and moderate level of social support from significant others (AOR=3.73; p=0.002; 95% CI=1.66-10.04) were the significant contributing factors to GAD among PLHIV. In conclusion, low level support systems and illicit substance use were profound contributing factors for GAD among PLHIV. Hence, addressing these two factors, in addition to conventional HAART treatment, is crucial to ensure optimum care of this group of patients.